2014
DOI: 10.1371/journal.pone.0097901
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin and Quercetin Affect the Cholesterol Absorption Mediated by Epithelial Cholesterol Transporter Niemann–Pick C1-Like 1 in Caco-2 Cells and Rats

Abstract: Niemann–Pick C1-Like 1 (NPC1L1) mediates cholesterol absorption, and ezetimibe is a potent NPC1L1 inhibitor applicable for medication of hypercholesterolemia. Epidemiological studies demonstrated that consumption of polyphenols correlates with a decreased risk for atherosclerosis due to their antioxidant effect. This activity can hardly be attributable to the antioxidant activity only, and we hypothesized that polyphenols inhibit intestinal transport of cholesterol. We elucidated the kinetic parameters of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 27 publications
3
68
1
1
Order By: Relevance
“…Previous studies have shown that luteolin administration suppresses serum cholesterol through downregulating npc1l1 and hmgcr expressions . Although reduced npc1l1 mRNA level was also observed in the luteolin‐treatment group in the present study, the plasma cholesterol and faecal lipid levels did not change.…”
Section: Discussioncontrasting
confidence: 70%
“…Previous studies have shown that luteolin administration suppresses serum cholesterol through downregulating npc1l1 and hmgcr expressions . Although reduced npc1l1 mRNA level was also observed in the luteolin‐treatment group in the present study, the plasma cholesterol and faecal lipid levels did not change.…”
Section: Discussioncontrasting
confidence: 70%
“…Although we did not test the effect of Q3G on NPC1, all of the other known processes of Ebola virus entry were not inhibited by Q3G. A recent study demonstrated that quercetin inhibited the actions of the receptor Niemann-Pick C1-like 1 by decreasing cholesterol uptake in HEK 293T cells (29). Although we did not look specifically at NPC1 expression or cholesterol levels in this study, it is possible that Q3G may affect a cholesterol-or NPC-1-related process and thereby prevent Ebola virus entry.…”
Section: Discussionmentioning
confidence: 79%
“…Similar to hesperidin, luteolin (Nekohashi et al, 2014;Kwon et al, 2015), quercetin (Nekohashi et al, 2014), catechins (Koo and Noh, 2007), and proanthocyanidins (Bladé et al, 2010) have shown an inhibitory effect on fat or cholesterol absorption. Various mechanisms may be involved in this capacity of flavonoids.…”
Section: Flavanonesmentioning
confidence: 99%